Transformasi Pendidikan Guru SD melalui Dakwah Islam Berkemajuan: Tinjauan Bibliografis pada Pendekatan Holistik dan Multikultural - Dedi Dwi Cahyono (Lembaga Yasin AlSys, 2025)
This study examines the transformation of elementary school teacher education through the Dakwah Islam Berkemajuan approach, which integrates progressive Islamic values into the education system to enhance teachers' spiritual competence, professionalism, and inclusivity. The research is grounded in the need for a holistic and multicultural education system capable of addressing contemporary challenges. The primary objective is to explore the potential of the Dakwah Islam Berkemajuan approach in shaping teacher education that is moderate and responsive to diversity. A Systematic Literature Review (SLR) was conducted using bibliographic analysis, supported by bibliometric mapping with VOSviewer. The findings indicate that this approach emphasizes the principles of moderation, tolerance, and respect for diversity within teacher education processes. Moreover, the study highlights the importance of collaboration between progressive dakwah and multicultural education to strengthen social harmony and support Muhammadiyah's educational mission. The main conclusion asserts that this approach holds transformative potential in creating an inclusive educational ecosystem that is adaptive to societal dynamics. The implications include the need to develop teacher training programs grounded in progressive Islamic values, enhance inter-institutional collaboration, provide professional mentoring, and formulate inclusive educational policies. The study also recommends further research to explore the implementation of this approach in other educational contexts.